2021
DOI: 10.1002/cti2.1257
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of the combination of axitinib and pembrolizumab‐activated autologous DC‐CIK cell immunotherapy for patients with advanced renal cell carcinoma: a phase 2 study

Abstract: Objectives. Although axitinib has achieved a preferable response rate for advanced renal cell carcinoma (RCC), patient survival remains unsatisfactory. In this study, we evaluated the efficacy and safety of a combination treatment of axitinib and a low dose of pembrolizumab-activated autologous dendritic cells-co-cultured cytokine-induced killer cells in patients with advanced RCC. Methods. All adult patients, including treatment-naive or pretreated with VEGF-targeted agents, were enrolled from May 2016 to Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Overall, mAb-targeted T-NK cells produced a significant improvement in cytotoxicity that was consistent with the levels of PD-L1 expression on target cells compared to the isotype control. PD-1 is as an inhibitory regulator of T-NK cells and is known to be upregulated on T-NK cells of cancer patients [31,32]. In this regard, blocking of the PD-1/PD-L1 axis improved the intrinsic cytotoxic activity of T-NK cells against PD-L1+ tumour cells, indicating another mode of avelumab action on lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, mAb-targeted T-NK cells produced a significant improvement in cytotoxicity that was consistent with the levels of PD-L1 expression on target cells compared to the isotype control. PD-1 is as an inhibitory regulator of T-NK cells and is known to be upregulated on T-NK cells of cancer patients [31,32]. In this regard, blocking of the PD-1/PD-L1 axis improved the intrinsic cytotoxic activity of T-NK cells against PD-L1+ tumour cells, indicating another mode of avelumab action on lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…PD‐1 is as an inhibitory regulator of T‐NK cells and is known to be upregulated on T‐NK cells of cancer patients [31, 32]. In this regard, blocking of the PD‐1/PD‐L1 axis improved the intrinsic cytotoxic activity of T‐NK cells against PD‐L1+ tumour cells, indicating another mode of avelumab action on lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our previous studies have shown that PD1-T cells were active in several kinds of solid tumor, including CRC. 18 , 19 After blocking the PD1/PD-L1 signal pathway with a low dose of pembrolizumab, the cytotoxicity of DC‐CIK cells was enhanced. 18 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…To overcome the immune barrier of the tumor microenvironment, we developed a novel PD‐1 blockade‐activated DC-CIK cells (hereafter referred to as PD1-T cells), which were manufactured by blocking the PD‐1 epitope in DC-CIK cells with a low-dose of anti-PD-1 antibody (pembrolizumab). 18 , 19 Our previous clinical trials indicated a good safety and efficacy for PD1-T cells in solid tumor. 18 , 19 Based on these findings, we conducted a randomized, multicenter, phase 3 trial to evaluate whether the addition of PD1-T cells to XELOX plus bevacizumab improves efficacy compared to XELOX plus bevacizumab alone in patients with previously untreated mCRC.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation